(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Children’s cartoons are the most popular kind of entertainment. In recent years, children have gotten considerably extra interested in cartoons, as well as it has becomes their main leisure. Children often begin viewing cartoons on television when they are six months old and become devoted viewers by the age of two or three. Children’s interest in cartoons has expanded dramatically over time, and it has become a popular pastime in some homes. This study is conducted using a questionnaire survey. Respondents came from a variety of schools and different parts of Delhi. Survey research is one of the most important domains of measurement in applied social research. The interviews, which included open-ended questions, focused on children’s behavior. An online survey was used to analyze the data, which was completed via online forms. A total of 100 people from various parts of Delhi were asked to participate in the research by filling out questionnaires. Children’s behavior was significantly influenced by watching cartoons and there were both bad and good changes. The majority of children respond in the same manner they do when they watch adults conduct things on television and emulate them in their daily lives. The future scope of this study is to spread awareness about the major impacts of the Watching TV cartoons program on children’s and how to save the children’s from its bad impacts.